Optimization of Combined Microwave and Ultrasound Extractions of Cannabinoids Compounds from Cannabis indica L. (Blueberry Cultivar) Using Response Surface Methodology - Hirunyasiri, Rossakornpat; Punamorntarakul, Natnakorn; Jintawiwat, Raweeroj; Pankasemsuk, Tanachai; Phramphun, Kriangsak; Loveemongkol, Rien; Supasin, Supakiat; Kawee-ai, Arthitaya (Progress in Applied Science and Technology, 2024)
Microwave and ultrasound are novel technologies that are widely used for extracting bioactive compounds from plant materials. In this study, combined extraction techniques, microwave and ultrasound, were applied to extract cannabinoids, cannabidiol (CBD) and delta-9-tetrahydrocannabinol (THC), from Cannabis indica L. (Blueberry cultivar). Three independent variables including solid to liquid ratio (X1, A: 1:10-1:30 w/v), microwave extraction time (X2, B: 5-20 min), and ultrasound extraction time (X3, C: 10-30 min) were optimized using central composite design (CCD). The experimental data obtained was fitted to a second-order polynomial equation using multiple regression analysis and additionally analyzed using appropriate statistical methods (analysis of variance, ANOVA). The optimum conditions were determined according to the solid to liquid ratio (X1, A) of 1:22 (w/v), microwave extraction time (X2, B) of 5 min and ultrasound extraction time (X3, C) of 14 min. Under these conditions, the experimental CBD and THC content was 0.298±0.001 mg/g dry weight and 91.35±0.35 mg/g dry weight, respectively. The experimentally-achieved values were in accordance with those estimated by the CCD model, suggesting the applicability of the utilized model and the favorable result of CCD’s application in the optimization of the combined microwave and ultrasound extraction.